Shapes and Rise Velocities of Single Bubbles in a Confined Annular Channel: Experiments and Numerical Simulations - Andrea Cioncolini; Mirco Magnini (Fluids, 2021)
Shapes and rise velocities of single air bubbles rising through stagnant water confined inside an annular channel were investigated by means of experiments and numerical simulations. Fast video imaging and image processing were used for the experiments, whilst the numerical simulations were carried out using the volume of fluid method and the open-source package OpenFOAM. The confinement of the annular channel did not affect the qualitative behavior of the bubbles, which exhibited a wobbling rise dynamic similar to that observed in bubbles rising through unconfined liquids. The effect of the confinement on the shape and rise velocity was evident; the bubbles were less deformed and rose slower in comparison with bubbles rising through unconfined liquids. The present data and numerical simulations, as well as the data collected from the literature for use here, indicate that the size, shape, and rise velocity of single bubbles are closely linked together, and prediction methods that fail to recognize this perform poorly. This study and the limited evidence documented in the literature indicate that the confinement effects observed in non-circular channels of complex shape are more complicated than those observed with circular tubes, and much less well understood.